2018
DOI: 10.1186/s41256-018-0091-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting access to primary health care services for persons with disabilities in rural areas: a “best-fit” framework synthesis

Abstract: BackgroundAccess to primary health care (PHC) is a fundamental human right and central in the performance of health care systems, however persons with disabilities (PWDs) generally experience greater barriers in accessing PHC than the general population. These problems are further exacerbated for those with disabilities in rural areas. Understanding PHC access for PWDs is particularly important as such knowledge can inform policies, clinical practice and future research in rural settings.MethodsWe conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 77 publications
(236 reference statements)
7
69
0
8
Order By: Relevance
“…Our findings agree with other publications describing acceptability as a dimension of access to healthcare [15][16][17]. This is particularly important and could help in resolving some misunderstandings surrounding the definition of acceptability.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings agree with other publications describing acceptability as a dimension of access to healthcare [15][16][17]. This is particularly important and could help in resolving some misunderstandings surrounding the definition of acceptability.…”
Section: Discussionsupporting
confidence: 91%
“…(5) Timeliness; (6) Acceptability; and (7) Awareness [14]. Dassah et al [16] applied this framework to explore the factors affecting access to primary healthcare for persons with disability. They also looked at how this framework can inform policies, clinical practices and future research projects [16].…”
Section: Acceptability Within the Context Of Access To Healthcarementioning
confidence: 99%
“…Mortality of other time-critical diseases, like stroke, may have the same risk. Another study showed that geography obstacles were one of the four major factors that persons with disabilities were unable to access primary health care [33]. Moreover, we found an obvious regional disparity in spatial accessibility to county hospital exist across the Shaanxi Province.…”
Section: Discussionmentioning
confidence: 63%
“…The relationship between health outcomes and disability is complicated and the provision of longterm care in everyday life for people living in resource limited settings is a major public health problem especially in developing countries where the prevention and the health service is very scarce [16]. Moreover, negative attitude towards and stereotyping of PwDs limit educational and employment opportunity that creates dependency and exclusion of PwDs [27], and this was noted in the current study.…”
Section: Discussionmentioning
confidence: 70%
“…In Ethiopia, about 46% of PwDs are women [14] and they, for instance, carry the double burden of stereotypes, discrimination and economic challenges associated with being women and person with disability. Age is also a factor whereby children with disabilities (CwDs) are less likely to attend schooling or access healthcare services leaving them vulnerable to poverty and poor health that substantially reduce their quality of life [15,16]. As a group, without underplaying variations within, PwDs are still among the most disadvantaged segment of the society.…”
Section: Promoting Inclusive and Sustainable Development Requires Remmentioning
confidence: 99%